Evaluasi Hi-fer+Are Bolong dan Kumpai Tembaga dengan Suplementasi Kemon Air terhadap Nilai Kecernaan Secara In Vitro - Muhakka, Muhakka; Imsya, A; Tunggal, T; Riswandi, Riswandi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Muhakka M, Imsya A, Tunggal T, Riswandi R. 2022. Evaluation of hi-fer+are bolong and kumpai tembaga with kemon air supplementation on digestibility value in vitro. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 816-823. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Forage is the main feed for ruminants whose availability is addictive to the season, so it is necessary to find an alternative by utilizing swamp forage by fermentation. This study aimed to determine the nutritional value of fermented forage (Hi-fer+) Are Bolong and Kumpai tembaga with Kemon Air Supplementation on in vitro Digestibility Value. This study used a completely randomized design with 4 treatments and 3 replications, with the following treatments: (A) Hi-fer+Are Bolong 100% + Kumpai tembaga 0% + Kemon air 0%; (B) Hi-fer+ Are Bolong 75% + Kumpai tembaga 20% + Kemon Air 5%; (C) Hi-fer+Are Bolong 50% +Kumpai tembaga 40% + Kemon Air 10% and (D) Hi-fer+Are Bolong 25% +Kumpai tembaga 60% + 15% Kemon Air. The results showed that the treatment had a notable effect on the digestibility of dry matter, organic matter and NH3, but had no significant outcome on the pH content. The best results were in treatment C, namely: Hi-fer+Are perforated 50%, Kumpai tembaga 40% and Kemon air 10% which gave the best digestibility value.